2019
DOI: 10.21470/1678-9741-2018-0351
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Perventricular and Percutaneous Device Closure Treatments for Isolated Ventricular Septal Defect: A Chinese Single-Institution Experience

Abstract: Objectives To compare the advantages and disadvantages of perventricular and percutaneous procedures for treating isolated ventricular septal defect (VSD). Methods A total of 572 patients with isolated VSD were selected in our hospital between January 2015 and December 2016. The patients’ median age and weight were five years (1-26 years) and 29 kg (9-55 kg), respectively. The median diameter of VSD was 6.0 mm (5-10 mm). Patients were divided into two groups. In group A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…Although few patients had transitory rhythm disturbances during the study, some of them returned with complete AV block and had a pacemaker implanted permanently. Some authors have mentioned that, in case of early complete AV block due to mechanical injury during manipulation of the delivery system or during device implant, conversion to open surgery should be considered [ 7 , 10 ]. The cause of late-onset complete AV block remains unknown, but it probably occurs as a result of chronic inflammation and fibrosis due to the device, which is more likely to occur in infants with large defects.…”
Section: Discussionmentioning
confidence: 99%
“…Although few patients had transitory rhythm disturbances during the study, some of them returned with complete AV block and had a pacemaker implanted permanently. Some authors have mentioned that, in case of early complete AV block due to mechanical injury during manipulation of the delivery system or during device implant, conversion to open surgery should be considered [ 7 , 10 ]. The cause of late-onset complete AV block remains unknown, but it probably occurs as a result of chronic inflammation and fibrosis due to the device, which is more likely to occur in infants with large defects.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure has been shown to be safe and feasible in the setting of AR. In a recent review for the safety of device closure for VSD, it was found that percutaneous and perventricular device closure for VSD are safe and did not have any extra morbidity [ 15 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Comparing transthoracic and transcatheter device closure of VSD, the transthoracic procedure provides a shorter path and a more perpendicular angle to the defect. [23] During both procedures of device closure, the most important step is to guide the wire through the VSD to establish the delivery track. Based on our experience with color Doppler imaging by TEE, the wire was easy to aim toward and through the VSD during the transthoracic procedure.…”
Section: Discussionmentioning
confidence: 99%